L'hippodrome de Constantinople. Essais de restitution architecturale du dernier état du monument - Golvin, Jean-Claude; Fauquet, Fabricia (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2008)
Abstract Until now, all the circus reconstruction’s attempts were confronted to the same problem: the lack of a complete comparative study able to give all the necessary arguments to support the given hypothesis. In our previous works, we have just achieved a comparative and functional study of the Roman’s circus to explain the strong links between the function and the shape of this edifice for the Roman spectacles. This comparative and functional study produced a large set of useful informations allowing an architectural reconstruction of Constantinople’s Hippodrome. This study seemed essential because this major building has not been described in the fundamental work of J. H. Humphrey, nor in recent studies, mainly those of Guilland and Dagron, allow a new reading of this monument. Regarding the archaeological data, only few parts of the hippodrome are known. These data were compared with recent studies and ancient sources, the book of the ceremonies from Constantin Porphyrogenitus. The accuracy of the information provided by the text allows to understand the functioning of the building and to reconstruct a large portion of its components (cavea, spina, kathisma and carceres). Thanks to this study, we have gained a clear idea of the architecture of the latest state of the Constantinople’s hippodrome.